A new V-doped Bi2(O, S)3 oxysulfide catalyst for highly efficient catalytic reduction of 2-nitroaniline and organic dyes. (December 2017) - Abay, Angaw Kelemework; Kuo, Dong-Hau; Chen, Xiaoyun; Saragih, Albert Daniel
Abstract: A new type of convenient, and environmentally friendly, Vanadium (V)-doped Bi2 (O, S)3 oxysulfide catalyst with different V contents was successfully synthesized via a simple and facile method. The obtained V-doped Bi2 (O, S)3 solid solution catalysts were fully characterized by conventional methods. The catalytic performance of the samples was tested by using the reduction of 2-nitroaniline (2-NA) in aqueous solution. The reduction/decolorization of methylene blue (MB) and rhodamine B (RhB) was also chosen to evaluate the universality of catalysts. It was observed that the introduction of V can improve the catalytic performance, and 20%V-Bi2 (O, S)3 was found to be the optimal V doping concentration for the reduction of 2-NA, MB, and RhB dyes. For comparative purposes, a related V-free Bi2 (O, S)3 oxysulfide material was synthesized and tested as the catalyst. The superior activity of V-doped Bi2 (O, S)3 over pure Bi2 (O, S)3 was ascribed mainly to an increase in active sites of the material and also due to the presence of synergistic effects. The presence of V 5+ as found from XPS analysis may interact with Bi atoms and enhancing the catalytic activity of the sample. In the catalytic reduction of 2-NA, MB and RhB, the obtained V-doped Bi2 (O, S)3 oxysulfide catalyst exhibited excellent catalytic activity as compared with other reported catalysts. Furthermore this highly efficient, low-cost and easily reusable V-doped Bi2 (O, S)3 catalyst is anticipated to be of great potential in catalysis in the future. Graphical abstract: The catalytic reduction of 2-NA, RhB and MB dyes over the 20%V-Bi2 (O, S)3 oxysulfide catalyst with NaBH4 in aqueous solution. Highlights: A new V-doped Bi2 (O, S)3 solid-solution catalysts was synthesized by a feasible method. V-doped Bi2 (O, S)3 was first used as a catalyst for the reduction 2-NA, MB and RhB dyes. We compare catalytic activity of Bi2 (O, S)3 and V-doped Bi2 (O, S)3 catalysts in our study. V-doped Bi2 (O, S)3 catalysts showed much enhanced catalytic activity than pure Bi2 (O, S)3. The reduction of mixture of dyes become more effective with V-doped Bi2 (O, S)3 catalyst.